Development of MOST, a fast simulation model for optimisation of floating offshore wind turbines in Simscape Multibody. Issue 1 (1st April 2022) - Sirigu, M.; Faraggiana, E.; Ghigo, A.; Bracco, G.
Abstract: the paper presents the development of an innovative non-linear, time domain numerical model for the simulation of offshore floating wind turbines, named MOST. The model is able to evaluate the movement of the platform in six degrees of freedom, the power production and the load cycles acting on the blades. MOST is implemented in Matlab-Simulink environment using Simscape Multibody. The aerodynamics is modelled with the blade element momentum theory and the hydrodynamics is modelled using WEC-Sim, a Simscape library developed by NREL and SANDIA. The use of Simscape offers great flexibility to quickly introduce complex dynamic systems such as hybrid wave-wind platforms, flexible platforms, or sea water active ballast systems. Additionally, Matlab provides useful toolboxes and extensive libraries for advanced control systems, linearisation analysis, parallelisation and generation of C code. The results of MOST are then compared to FAST, an open-source code widely used in the academic research. The case study is a 15 MW reference wind turbine installed on the Volturn US platform. The comparison shows a good agreement between the two codes with a significant reduction of the simulation time.